2012
DOI: 10.1098/rsfs.2012.0021
|View full text |Cite
|
Sign up to set email alerts
|

Criticality and the onset of ordering in the standard Vicsek model

Abstract: Experimental observations of animal collective behaviour have shown stunning evidence for the emergence of large-scale cooperative phenomena resembling phase transitions in physical systems. Indeed, quantitative studies have found scale-free correlations and critical behaviour consistent with the occurrence of continuous, second-order phase transitions. The standard Vicsek model (SVM), a minimal model of self-propelled particles in which their tendency to align with each other competes with perturbations contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…11. This could explain why some studies of the Vicsek model in the small velocity region claim to find a critical transition [33]: as one gets closer and closer to the zero speed limit, the system-size above which one can correctly observe the discontinuous nature of the transition diverges.…”
Section: E Order Parameter and Finite-size Scalingmentioning
confidence: 95%
“…11. This could explain why some studies of the Vicsek model in the small velocity region claim to find a critical transition [33]: as one gets closer and closer to the zero speed limit, the system-size above which one can correctly observe the discontinuous nature of the transition diverges.…”
Section: E Order Parameter and Finite-size Scalingmentioning
confidence: 95%
“…The Vicsek model exhibits, at least for not-too-large sizes, a wide regime where correlations peak at the transition and finite-sizescaling holds(Baglietto et al, 2012;Grégoire and Chaté, 2004;Vicsek et al, 1995).…”
mentioning
confidence: 99%
“…On increasing noise there is known to be a transition between the ordered and disordered phase [7]. The nature of this, and similar, transitions has been studied in depth [7][8][9][10][11][12][13][14][15][16] and recent studies have shown that the phase transition of the standard Vicsek model is continuous when the velocity is small [12][13][14]; and it has been argued that large velocities can lead to artefacts related to the boundary conditions [16]. The nature of the transition has also been shown to depend intimately on the type of noise added to the particles [17], which can either be 'angular', where a random angle is added to the orientation of the velocity of a particle, or 'vectorial', in which a random vector is added to the velocity of a particle.…”
mentioning
confidence: 99%